2015
DOI: 10.1016/j.vaccine.2015.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of pneumococcal polysaccharide vaccination on nasopharyngeal carriage in children previously vaccinated with various pneumococcal conjugate vaccine regimes

Abstract: Previously, the Fiji Pneumococcal Project (FiPP) evaluated reduced dose immunization schedules that incorporated pneumococcal protein conjugate and/or polysaccharide vaccine (PCV7 and 23vPPV, respectively). Immune hyporesponsiveness was observed in children vaccinated with 23vPPV at 12 months of age compared with children who did not receive 23vPPV. Here we assess the long-term impact of 23vPPV vaccination on nasopharyngeal carriage rates and densities of Streptococcus pneumoniae, Haemophilus influenzae, Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Our previous studies in Fiji [25, 30] found significant differences in bacterial carriage between iTaukei and FID children but only examined a limited number of bacterial species. Here, we found substantial differences in the entire nasopharyngeal microbiota based on ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies in Fiji [25, 30] found significant differences in bacterial carriage between iTaukei and FID children but only examined a limited number of bacterial species. Here, we found substantial differences in the entire nasopharyngeal microbiota based on ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that social contact can influence microbiota [41] but the relative importance of social contact compared with other factors as a determinant of microbiota is unknown. In Fiji, the two main ethnic groups have similar household income [30] so it is unlikely that socio-economic status, a known risk factor for pneumococcal carriage [23], contributes to the observed differences in nasopharyngeal bacteria between iTaukei and FID children. Given the complexity and interconnected nature of factors that can determine microbiota, it is likely multiple factors are involved in the underlying differences in microbial composition between ethnic groups in Fiji.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These conjugates induce robust, T-dependent antibody responses in young children. Routine immunizations with the pneumococcal conjugate vaccine have resulted in highly significant reductions in pneumococcus bacteremia among young children [4, 5]. …”
Section: Introductionmentioning
confidence: 99%